PENERAPAN SISTEM INFORMASI VISUALISASI DATA INDUSTRI KECIL MENENGAH DENGAN MENGGUNAKAN METODE DASHBOARD : STUDI KASUS DINAS KOPERASI UKM & PERINDUSTRIAN KABUPATEN OGAN KOMERING ILIR - Muhamad Diki; Fitri Purwaningtias (P3M Institut Teknologi Pagar Alam, 2023)
This research aims to implement a data visualization information system for small and medium industries (IKM) using the dashboard method. The case study was carried out at the Ogan Komering Ilir Regency Cooperative, SME and Industry Service, with the aim of assisting decision making in the small and medium industry sector. The dashboard method is used to present small and medium industry data visually and interactively, making it easier for users to understand the data and make the right decisions. This research uses a qualitative approach with data collection techniques through observation, interviews and documentation. The results of the research show that the application of a data visualization information system for small and medium industries using the dashboard method can help decision making at the Ogan Komering Ilir Regency Cooperatives, SMEs and Industry Department more quickly and accurately. Apart from that, this system can also provide more complete and integrated information, so that it can increase the efficiency and effectiveness of the performance of the Ogan Komering Ilir Regency Cooperatives, SMEs and Industry Service. Keywords: Tableau, IKM, UMKM, Dashboard.